The Instrumented Sit-to-Stand Test (iSTS) Has Greater Clinical Relevance than the Manually Recorded Sit-to-Stand Test in Older Adults - van Lummel, Rob C (PUBLIC LIBRARY SCIENCE, 2022)
10.1371/journal.pone.0157968